EXPANDING THE OPPORTUNITIES OF KAZAKHSTAN’S EDUCATION THROUGH INTEGRATION OF ICT - Ulman, M.; Aldabergenova, A.O.; Yessengabylov, I.Zh.; Kabdualiyev, D.K.; Salgozha, I.T. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The article presents the possibilities of expanding Kazakhstan`s education through the integration of information and communication technologies (ICT) in educational institutions. Possible ways to solve the problem and implement the implementation of ICT in the education system of Kazakhstan are presented, through investments in infrastructure and technology, training and support for teachers and students, as well as the development of digital content and resources that comply with national curricula and standards. It also outlines that a virtual laboratory is a computer-based environment that simulates laboratory work and allows students to conduct experiments and learn scientific concepts, and describes the benefits of a virtual laboratory. They are concluded to improve educational outcomes in STEM subjects and provide opportunities for international collaboration and research.